Problems Faced by English Language Teachers on Transfer of Training Skills - Bhandari, Bhim Lal; Bhandari, Laxman Prasad (Lumbini Journal of Language and Literature, 2024)
Transfer of training is a continuous process of applying the content, instructional knowledge, and skills learned during the training session into classroom practice. This study explored problems faced by secondary-level English language teachers on the transfer of training abilities in their classroom practices. The study was conducted using a narrative inquiry method applying unstructured interviews to get the required information. Four trained English language teachers teaching in four public schools in Rupandehi district were selected purposively. This research revealed pedagogical transformation through training was not satisfactory as the teachers partially transferred the learned knowledge and skills from training in the classroom delivery. Moreover, poor resources and overload, ineffective curriculum and TPD (Teacher professional development) training, poor collaborative culture, and inadequate administrative support were some problems to increase the rate of transfer of training skills. The study can contribute to providing insightful ideas to the teachers in the transformation of training skills.